2014
DOI: 10.2174/1567202610666131125000506
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Vascular Differences among Patients Suffering from Multiple Sclerosis

Abstract: The aim of our study was to analyze morphological and functional aspects of cerebral veins by means of ecocolor-Doppler in young (i.e., ≤ 30 years old) and older (i.e., >30 years old) patients suffering from multiple sclerosis. 552 multiple sclerosis patients were evaluated by means of a dedicated Echo-Color-Doppler support (MyLab Vinco echocolor Doppler System, Esaote), in both supine and sitting positions. 458 (83%) showed alterations in their morphological and functional structures of cerebral veins and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…It is possible that this is also the cause of neurodegeneration in AD. A recent finding on evaluation of MS which is similar to AD suggests that age may be a significant contribution to the disease development of MS [19,20,22]. Moreover, it is demonstrated that the longer the duration of the disease, the higher the damage of the vascular tissues and hence the greater the degree of disability [19].…”
Section: Causes Of Alzheimer's Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…It is possible that this is also the cause of neurodegeneration in AD. A recent finding on evaluation of MS which is similar to AD suggests that age may be a significant contribution to the disease development of MS [19,20,22]. Moreover, it is demonstrated that the longer the duration of the disease, the higher the damage of the vascular tissues and hence the greater the degree of disability [19].…”
Section: Causes Of Alzheimer's Diseasementioning
confidence: 99%
“…The younger patients aged 30 years and lower, show cerebral veins stenosis and blocked flow of blood in internal jugular veins and vertebral veins compared to the older patients aged 30 years and above. It was established that only the duration of the disease can be able to explain the disease differences [19].…”
Section: Characteristics Of Alzheimer's Diseasementioning
confidence: 99%
See 3 more Smart Citations